Strengthening safety regulations for e-marketing of herbaceutical products / Nurzahidah Jaapar ... [et al.] - Jaapar, Nurzahidah; Borhan, Farrah Payyadah; Moidin, Shofiyyah; Syed Abdullah, Sharifah Fadylawaty (Academy of Contemporary Islamic Studies (ACIS), Universiti Teknologi MARA (UiTM), 2025)
In the realm of marketing, relevant stakeholders need to consider the potential consequences of non-compliance with stipulated regulations. These consequences include adverse impacts resulting from advertisements, the exploitation of certain demographics, detrimental effects on public health, and violations of legal statutes. Hence, it is essential to ensure that all aspects of e-marketing are thoroughly validated in accordance with relevant regulations and legal frameworks before its publication. This article aims to explore marketing trends for herbaceutical products and evaluate the safety regulations governing emarketing in Malaysia. Several authorities were interviewed, and selected regulations were examined to determine whether appropriate safety measures were implemented. The findings suggest that certain regulations require reassessment to enhance safety regulations for the emarketing of herbaceutical products.